Analysis of Case-Based Learning Assisted by Math Song Media on Students' Mathematical Literacy - Dhiyazzahra, Daffani Putri; Ubaidah, Nila; Maharani, Hevy Risqi (Jurnal Pendidikan Matematika, 2023)
The 2018 PISA results show that Indonesia ranked 74th out of 79 participating countries. The rationale behind this lies in the fact that students are unaccustomed to engaging with mathematical literacy questions, particularly those concerning two-dimensional geometric shapes. Furthermore, the instructional model employed does not yet adhere to a student-centred approach. The study aimed to analyze and determine the effectiveness of case-based learning assisted by math song media on students' mathematical literacy in the material of geometric shapes of cubes and blocks at State MTs Negeri 2 Semarang City. The research method was a mixed method-exploratory sequential design. The population was all students of class VIII MTs Negeri 2 Semarang City. The sampling technique was purposive sampling, with 32 students of class 8th grade B as the sample. The research instruments included observation sheets, questionnaires, interview guides, and mathematical literacy tests. Qualitative data analysis techniques were data reduction, data presentation, and conclusion and quantitatively using the normality test, Paired Sample t-test, and N-Gain test. The percentage of students interested in learning was 78.4%, and the teacher's response questionnaire was perfect, 88.9%. The acquisition of the Paired Sample t-test was Sig. (2-tailed) 0.000 means 0.000 <0.05 Ha accepted; in conclusion, there is a difference in mathematical literacy's pre-test and post-test averages, increasing from 53.06 to 86.34. The N-Gain test results obtained 0.7 with a percentage of 65.1% in the category of quite effective. Applying this learning, students are involved in learning and trained to analyze the case's problems critically. Hasil PISA 2018 menunjukkan peringkat ke 74 dari 79 negara partisipan. Penyebabnya siswa tidak dibiasakan mengerjakan soal-soal yang berkaitan dengan literasi matematika khususnya pada materi bangun ruang sisi datar dan model pembelajaran yang digunakan belum bersifat student center. Tujuan penelitian untuk menganalisis dan mengetahui keefektifan case-based learning berbantuan media lagu matematika terhadap literasi matematis siswa pada materi bangun ruang sisi datar kubus dan balok di MTs Negeri 2 Kota Semarang. Metode penelitian adalah mixed method-exploratory sequential design. Populasi adalah seluruh siswa kelas VIII MTs Negeri 2 Kota Semarang. Teknik pengambilan sampel adalah purposive sampling dengan sampel yang digunakan adalah 32 siswa kelas VIII B. Instrumen penelitian yaitu lembar observasi, angket, pedoman wawancara, dan tes literasi matematis. Teknik analisis data kualitatif adalah reduksi data, penyajian data, dan penarikan kesimpulan dan kuantitatif menggunakan uji normalitas, Paired Sample t-Test, dan uji N-Gain. Siswa tertarik dengan pembelajaran, persentase 78,4% dan angket respon guru sangat baik, persentase 88,9%.  Perolehan Paired Sample t-Test yaitu Sig. (2-tailed) 0,000 artinya 0,000 < 0,05 maka  diterima, simpulannya ada perbedaan rata-rata pre-test dan post-test literasi matematis meningkat dari 53,06 sampai 86,34. Hasil uji N-Gain diperoleh 0,7 dengan persentase sebesar 65,1% dengan kategori cukup efektif. Penerapan pembelajaran membuat siswa terlibat dalam pembelajaran dan siswa terlatih untuk menganalisis kritis terhadap persoalan dalam kasus.